-4g=-36

Simple and best practice solution for -4g=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4g=-36 equation:


Simplifying
-4g = -36

Solving
-4g = -36

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '-4'.
g = 9

Simplifying
g = 9

See similar equations:

| n-15=-21 | | 3(2b-4)+14=26 | | 42=12+5(x-1) | | 192=72x^2+24X | | 6(x+3)-75=5(x-10) | | 5-5x=-8x+14 | | (12-15)3= | | 192=72x^2+24 | | 2x+3(x-4)=(x-3) | | A+BX=CX+D | | 4(Z+7)-6=2 | | 29-(-q)=86 | | xsquared+8x-5=15 | | g-13.37=-23 | | (0.5)(y)=3 | | 5y=175 | | 3(x-1)+60=8(x+4) | | g(-3)=2x-5 | | -30+6x=x | | -19-r=-57 | | y+17.5=49 | | -1+6x+x=-85 | | Q-65=875 | | (4+3x)(2-x)+(4-3x)(2+x)=22 | | 5x-2+4x=43 | | w+-28=-17 | | -38=-x+4x-5 | | 22x=44y | | 17y-12y=25 | | 3x-4-8x+12= | | 15-4X=-X | | 3(x-3)+5=4(x-2)-10 |

Equations solver categories